How  I solve:  `4*log_a 6-3*log_a 5-4*log_a 2` =

Expert Answers
justaguide eNotes educator| Certified Educator

The expression 4*log_a 6 -3log_a 5 - 4*log_a 2 has to be simplified.

Use the property a*log b = log b^a, log a+ log b = log(a*b) and log a - log b = log(a/b)

`4*log_a 6 -3log_a 5 - 4*log_a 2`

= `log_a 6^4 - log_a 5^3 - log_a 2^4`

= `log_a (6^4/(5^3*2^4))`

= `log_a (81/125)`

The required result is `log_a (81/125)`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question